SINTASAN DAN PERTUMBUHAN IKANPATIN SIAM (Pangasianodon hypopthalmus) AKIBAT RESPON FISIOLOGIS YANG BERBEDA PADA BERBAGAI TINGKAT KALSIUM MEDIA - Wyrantika, Cynthia Putu; ., Yulisman; Fitrani, Mirna (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT Soybean meal is plant protein sources that often used in fish feed. However, availability of soybean meal still depend on imports. Therefore, need an alternative to reduce dependence on soybean meal. Tofu waste can be used as alternative plant protein source. The aim of this research was to determine the best percentage of  fermented tofu waste meal in feed formulation for optimal growth and feed efficiency of catfish (Pangasius hypophthalmus) juvenile. This research was conducted at Laboratorium Dasar Perikanan, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University on August to October 2014 and the feed proximate analysis conducted in Laboratorium Bioproses, Department of Chemical Engineering, Faculty of Engineering, Sriwijaya University, Indralaya. The method of this research used Completely Randomized Design (CRD) with 6 treatments and 3 replications, consist of A (commercial feed), B (0% fermented tofu waste meal : 20% soybean meal), C (5%  fermented tofu waste meal : 15% soybean meal), D (10% fermented tofu waste meal : 10% soybean meal), E (15% fermented tofu waste meal : 5% soybean meal), F (20% fermented tofu waste meal : 0% soybean meal). The result showed that the use of fermented tofu waste in the feed had not signifficant on the growth of weight and length, specific growth rate, feed convertion ratio, feed efficiency, and survival rate of catfish juvenile for each treatment. The best result was obtained by treatment D which used  fermented tofu waste meal 10%.   Keywords : Pangasius hypophthalmus, fermented tofu waste, soybean meal, feed efficiency, growth